Recruitment of RNA Polymerase II to Metabolic Gene Promoters Is Inhibited in the Failing Heart Possibly Through PGC-1α (Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α) Dysregulation. (March 2019) - Bhat, Santosh; Chin, Adave; Shirakabe, Akihiro; Ikeda, Yoshiyuki; Ikeda, Shohei; Zhai, Peiyong; Hsu, Chiao-po; Sayed, Danish; Abdellatif, Maha; Byun, Jaemin; Schesing, Kevin; Tang, Fan; et al.
Abstract : Background: Proper dynamics of RNA polymerase II, such as promoter recruitment and elongation, are essential for transcription. PGC-1α (peroxisome proliferator-activated receptor [PPAR]-γ coactivator-1α), also termed PPARGC1a, is a transcriptional coactivator that stimulates energy metabolism, and PGC-1α target genes are downregulated in the failing heart. However, whether the dysregulation of polymerase II dynamics occurs in PGC-1α target genes in heart failure has not been defined. Methods and Results: Chromatin immunoprecipitation-sequencing revealed that reduced promoter occupancy was a major form of polymerase II dysregulation on PGC-1α target metabolic gene promoters in the pressure-overload–induced heart failure model. PGC-1α-cKO (cardiac-specific PGC-1α knockout) mice showed phenotypic similarity to the pressure-overload–induced heart failure model in wild-type mice, such as contractile dysfunction and downregulation of PGC-1α target genes, even under basal conditions. However, the protein levels of PGC-1α were neither changed in the pressure-overload model nor in human failing hearts. Chromatin immunoprecipitation assays revealed that the promoter occupancy of polymerase II and PGC-1α was consistently reduced both in the pressure-overload model and PGC-1α-cKO mice. In vitro DNA binding assays using an endogenous PGC-1α target gene promoter sequence confirmed that PGC-1α recruits polymerase II to the promoter. Conclusions: These results suggest that PGC-1α promotes the recruitment of polymerase II to the PGC-1α target gene promoters. Downregulation of PGC-1α target genes in the failing heart is attributed, in part, to a reduction of the PGC-1α occupancy and the polymerase II recruitment to the promoters, which might be a novel mechanism of metabolic perturbations in the failing heart.